Modeling Internal Erosion Processes in Soil Pipes: Capturing Geometry Dynamics - Nieber, J.L. (2020)
The flow of water in a soil pipe and the resulting erosion of the soil pipe wall is simulated using a numerical solution of the Reynolds‐averaged Navier–Stokes equations coupled with the well‐known linear excess shear stress equation and the governing equation for transport of suspended sediment in turbulent flow. The modeling results are compared with an experiment in which the entrance to the soil pipe constructed in a laboratory flume was subjected to a constant head of water in a reservoir. The modeled pipe discharge was in good agreement with the measured results when roughness was imposed on the pipe wall. The temporal growth of the soil pipe was in good agreement with the experimental results when using a soil erodibility coefficient of 0.0025 s/m. Several assumptions were made in model formulation, the most significant being that the soil pipe grows uniformly along its length and that no sediment deposition occurs. Recommendations for future work regarding these assumptions as well as others are discussed.